(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
The objective was to find the factors involve that contributes toward the noncompliance in the patientswith cardioâ€vascular diseases. This was descriptive in nature. Nishter Hospital, Multan. Patients admittedÂ in the cardio ward of the hospital were interviewed during the period of June 6, to August 6, 2013. TheÂ information regarding the demographics, level of education, and trust on doctors, medication taking behavior andÂ compliance were taken with the help of questionnaire. Statistical analysis was performed with the help of SPSSÂ 17 (SPSS Inc. Released 2008. SPSS Statistics for Windows, Version 17.0. Chicago: SPSS Inc).Of 200 respondents 65.0%were compliant and 35% were noncompliant. Key words: Compliance, literacy, noncompliance